Sugar‐regulated susceptibility of tomato fruit to Colletotrichum and Penicillium requires differential mechanisms of pathogenicity and fruit responses. (29th April 2020) - Ziv, Carmit; Kumar, Dilip; Sela, Noa; Itkin, Maxim; Malitsky, Sergey; Schaffer, Arthur A.; Prusky, Dov B.
Summary: Colletotrichum gloeosporioides and Penicillium expansum cause postharvest diseases in tropical and deciduous fruit. During colonization, C. gloeosporioides and P. expansum secrete ammonia in hosts with low sugar content (LowSC) and gluconic acid in hosts with high sugar content (HighSC), respectively, as a mechanism to modulate enhanced pathogenicity. We studied the pathogens interactions with tomato lines of similar genetic background but differing in their sugar content. Colletotrichum gloeosporioides showed enhanced colonization of the LowSC line with differential expression response of 15% of its genes including enhanced relative expression of glycosyl hydrolases, glucanase and MFS‐transporter genes. Enhanced colonization of P. expansum occurred in the HighSC line, accompanied by an increase in carbohydrate metabolic processes mainly phosphoenolpyruvate carboxykinase, and only 4% of differentially expressed genes. Gene response of the two host lines strongly differed depending on the sugar level. Limited colonization of HighSC line by C. gloeosporioides was accompanied by a marked alteration of gene expression compared the LowSC response to the same pathogen; while colonization by P. expansum resulted in a similar response of the two different hosts. We suggest that this differential pattern of fungal/host responses may be the basis for the differential of host range of both pathogens in nature.